Mitochondrial autophagy: molecular mechanisms and implications for cardiovascular disease - Li, Anqi; Gao, Meng; Liu, Bilin; Qin, Yuan; chen, Lei; Liu, Hanyu; Wu, Huayan; Gong, Guohua (Cell death & disease, 2022)
Mitochondria are highly dynamic organelles that participate in ATP generation and involve calcium homeostasis, oxidative stress response, and apoptosis. Dysfunctional or damaged mitochondria could cause serious consequences even lead to cell death. Therefore, maintaining the homeostasis of mitochondria is critical for cellular functions. Mitophagy is a process of selectively degrading damaged mitochondria under mitochondrial toxicity conditions, which plays an essential role in mitochondrial quality control. The abnormal mitophagy that aggravates mitochondrial dysfunction is closely related to the pathogenesis of many diseases. As the myocardium is a highly oxidative metabolic tissue, mitochondria play a central role in maintaining optimal performance of the heart. Dysfunctional mitochondria accumulation is involved in the pathophysiology of cardiovascular diseases, such as myocardial infarction, cardiomyopathy and heart failure. This review discusses the most recent progress on mitophagy and its role in cardiovascular disease.